2017
DOI: 10.1007/s00125-017-4508-8
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial detection of autoreactive CD8+ T cells with HLA-A2 multimers: a multi-centre study by the Immunology of Diabetes Society T Cell Workshop

Abstract: Our results suggest that, although combinatorial multimer assays are challenging, they can be implemented in multiple laboratories, providing relevant T cell frequency measurements. Assay reproducibility was notably higher in the single-centre setting, suggesting that biomarker analysis of clinical trial samples would be most successful when assays are performed in a single laboratory. Technical improvements, including further standardisation of cytometry platforms, will likely be necessary to reduce assay var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…We identified antigen-specific CD8 + T cells using a modified combinatorial Tmr staining approach based on the method described by Newell et al (26) (Supplemental Figure 1). In verifying Tmr staining by CyTOF, we found that the intensity of Tmr staining was generally greater for the virus-specific pool than for the islet-specific pool (Supplemental Figure 1D and Figure 1A) and that both the Tmr + frequencies and the intensities of markers were highly reproducible (Supplemental Figure 2), as previously described with flow cytometric Tmr analysis (11)(12)(13)(14)(15).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…We identified antigen-specific CD8 + T cells using a modified combinatorial Tmr staining approach based on the method described by Newell et al (26) (Supplemental Figure 1). In verifying Tmr staining by CyTOF, we found that the intensity of Tmr staining was generally greater for the virus-specific pool than for the islet-specific pool (Supplemental Figure 1D and Figure 1A) and that both the Tmr + frequencies and the intensities of markers were highly reproducible (Supplemental Figure 2), as previously described with flow cytometric Tmr analysis (11)(12)(13)(14)(15).…”
Section: Resultssupporting
confidence: 75%
“…Ample evidence indicates that islet-specific CD8 + T cells are a significant driver of β cell destruction in T1D (34). However, across numerous studies involving individuals with T1D, the frequencies of islet-specific CD8 + T cells in peripheral blood have been neither consistently altered nor strongly correlated with disease progression (11)(12)(13)(14)(15)35). Here, through an unbiased and multidimensional approach, we demonstrate that islet-specific CD8 + T cells of HCs and T1D subjects comprise 3 dominant phenotypes that display characteristics of transitional memory or exhausted memory cells.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Tetramers Fluorochrome-labelled peptide-HLA-A2 tetramers were assembled from monomers from NIH Tetramer Core Facility (Atlanta, GA, USA) and streptavidin Qdots (Thermo Fisher Scientific, Waltham, MA, USA). Tetramer staining was performed as described previously [19]. Briefly, thawed PBMCs were treated with 50 nmol/l dasatinib for 15 min at 37°C, then pelleted and resuspended in tetramer Qdot master mix for 15 min at 37°C (details in ESM Table 2).…”
Section: Methodsmentioning
confidence: 99%